Preventing Foodborne Illness: Norovirus - Rachael Silverberg; Melissa K. Jones; Renée Goodrich Schneider; Aswathy Sreedharan; Keith R. Schneider (EDIS)
If you have ever had the stomach flu, norovirus was likely the culprit. Norovirus is the most common cause of foodborne illness in the United States and is transmitted through direct person-to-person contact or contaminated objects and food. This revised 5-page fact sheet covers how norovirus is spread, foods associated with norovirus, symptoms of infection, who is at risk, as well proper sanitation methods for preventing the spread of norovirus. Written by Rachael Silverberg, Melissa K. Jones, Renée Goodrich Schneider, Aswathy Sreedharan, and Keith R. Schneider, and published by the UF Food Science and Human Nutrition Department, June 2015.